Efficacy of Giant River Prawn Macrobrachium rosenbergii in Controlling the Invasive Snail Pomacea canaliculata: Implications for Ecological Farming - Yingying Wang; Yixiang Zhang; He Lv; Qiang Sheng (Diversity, 2023)
The invasive golden apple snail Pomacea canaliculata has a strong reproductive capacity and has rapidly spread in Asian countries. Current control methods include physical, chemical, and biological approaches, but there has been limited research on the control of P. canaliculata in its different life stages. This study assessed the effectiveness of using giant river prawns Macrobrachium rosenbergii in controlling juveniles of P. canaliculata through a controlled indoor experiment. The density, size, and dispersal range of recently hatched juvenile snails were significantly lower among those kept with prawns than those kept without prawns, indicating a control effect of M. rosenbergii at least on P. canaliculata juveniles. Furthermore, the study speculates on the potential application of M. rosenbergii in the context of a rice–prawn symbiotic system of ecological farming to control invasive P. canaliculata. In terms of effectiveness and safety, its application might lead to a win-win situation for both rice-farm profits and the ecological benefits of invasive species control.